Metagenomic Analysis of Fecal Archaea, Bacteria, Eukaryota, and Virus in Przewalski's Horses Following Anthelmintic Treatment - Hu, Dini; Yang, Jianming; Qi, Yingjie; Li, Boling; Li, Kai; Mok, Kai Meng (Frontiers in Veterinary Science, 2021)
Intestinal microbiota is involved in immune response and metabolism of the host. The frequent use of anthelmintic compounds for parasite expulsion causes disturbance to the equine intestinal microbiota. However, most studies were on the effects of such treatment on the intestinal bacterial microbes, none is on the entire microbial community including archaea, eukaryotic, and viral community in equine animals. This study is the first to explore the differences of the microbial community composition and structure in Przewalski’s horses prior to and following anthelmintic treatment, and to determine the corresponding changes of their functional attributes based on metagenomic sequencing. Results showed that in archaea, the methanogen of Euryarchaeota was the dominant phylum. Under this phylum, anthelmintic treatment increased the Methanobrevibacter genus and decreased the Methanocorpusculum genus and two other dominant archaea species, Methanocorpusculum labreanum and Methanocorpusculum bavaricum. In bacteria, Firmicutes and Bacteroidetes were the dominant phyla. Anthelmintic treatment increased the genera of Clostridium and Eubacterium and decreased those of Bacteroides and Prevotella and dominant bacteria species. These altered genera were associated with immunity and digestion. In eukaryota, anthelmintic treatment also changed the genera related to digestion and substantially decreased the relative abundances of identified species. In virus, anthelmintic treatment increased the genus of unclassified_d__Viruses and decreased those of unclassified_f__Siphoviridae and unclassified_f__Myoviridae. Most of the identified viral species were classified into phage, which were more sensitive to anthelmintic treatment than other viruses. Furthermore, anthelmintic treatment was found to increase the number of pathogens related to some clinical diseases in horses. The COG and KEGG function analysis showed that the intestinal microbiota of Przewalski's horse mainly participated in the carbohydrate and amino acid metabolism. The anthelmintic treatment did not change their overall function, however, it displaced the population of the functional microbes involved in each function or pathway. These results provide a complete view on the changes caused by anthelmintic treatment in the intestinal microbiota of the Przewalski’s horses.